Pool more, drive less: An investigation of barriers and motivators of ridepooling in autonomous vehicles - Nora Studer; Dorothea Schaffner; Nicole Haiderer; Annalisa Stefanelli; Michael A.B. van Eggermond; Alexander Erath (Transportation Research Interdisciplinary Perspectives)
The integration of on-demand ridepooling services provided by autonomous vehicles into transportation systems offers a solution to mobility challenges in the future. If such services effectively enable travellers to share a vehicle instead of driving alone, higher vehicle occupancy rates would lead to a more efficient use of existing road infrastructure. This in turn could help alleviate traffic congestion and its associated drawbacks. The acceptance of such autonomous ridepooling (aRP) services by prospective users is essential for their successful adoption. Therefore, this qualitative study aims to uncover the relevant factors that determine aRP acceptance and to better understand the drivers and barriers of aRP acceptance using a user-centered approach. Through 18 semi-structured in-depth interviews with a diverse range of participants, the study revealed the significance of performance expectations with regards to safety, comfort, flexibility, sustainability, and social aspects in shaping acceptance for aRP. Notably, ambivalent attitudes and controversial perceptions of these factors as well as differences between public transport and private car users underscore the importance of customer segmentation and tailored strategies for the design and promotion of aRP services. Findings emphasize the need for aRP services to prioritize user-centric approaches to enable the adoption and facilitate the integration of aRP as a more sustainable option into future transportation systems.